Determining hyporheic removal rates of trace organic compounds using non-parametric conservative transport with multiple sorption models. (1st November 2021) - Höhne, Anja; Lewandowski, Jörg; Schaper, Jonas L.; McCallum, James L.
Highlights: Shape of residence time distribution is crucial for estimating compound reactivity. Shaped residence time distribution functions introduce flawed transport properties. Joint parent-daughter simulation can identify dominant transformation-pathways. Daughter reaction rate may be underestimated if its parent transformation is ignored. Graphical abstract: Abstract: Assessing the transport and reactive processes of contaminants in freshwater streams is crucial in managing water resources sustainably. Particularly the hyporheic zone, the sediment-water interface where surface water and groundwater mix, may possess significant contaminant removal capacities due to its myriad physical, chemical, and microbiological processes. However, modelling approaches aiming at assessing the hyporheic zone's reactivity are either based on simple assumptions, such as, predefining the shape of the residence times distribution (RTD) function, or are computationally not feasible due to a too detailed system characterisation. In addition, parent-daughter reactions of contaminants are barely investigated. The present study introduces a numerical modelling framework for assessing hyporheic reactions of contaminant transformation reactions based on a non-parametric residence time approach combined with multiple sorption models and first-order removal reactions. The proposed framework uses natural electrical conductivity fluctuations to determine conservative transport properties and is demonstrated by interpreting time series of hyporheic point measurements of trace organic compounds, such as pharmaceuticals, and their transformation products using two commonly-used sorption models, namely the simple retardation and the first-order kinetic sorption model. The developed approach gives similar reaction rate coefficient estimates for all contaminants considered for both sorption models tested. The findings highlight that (i) the accurate shape of the RTD is most certainly important for reactive parameter determination and (ii) the daughter reaction rate coefficient may be underestimated if its parent transformation is ignored. The model provides reactive parameter estimates of contaminant transformation reactions with high parameter identifiability and informs which specific parent-daughter-pathway has occurred.